Aphelocheirus (s.str.) bruneiensis sp.n., a new benthic water bug (Hemiptera: Heteroptera: Aphelocheiridae) from Brunei, and a key to Bornean Aphelocheirus - Zettel, Herbert; Lane, David J. W.; Moore, Stephen (Zootaxa, 2008)
Aphelocheirus (s.str.) bruneiensis sp.n. from Brunei is described and illustrated; its type locality is described in detail. Aphelocheirus (s.str.) kinabalu Polhemus & Polhemus, 1989 is recorded from Sarawak for the first time. An identification key to the brachypterous morphs of the six species known from Borneo is presented. Digital photographs of the new species and three other rare species are provided.